0 - Prelim - Africa Development, (Africa Development, 2021)
La révolution verte au Rwanda : au-delà de la dichotomie domination et émancipation Aymar Nyenyezi Bisoka.............................................................................................. ............................................................1 Acquiring Pedagogic Authority While Learning to Teach Zahraa McDonald, Yusuf Sayed, Tarryn de Kock & Nimi Hoffmann.................23 Dimensions of University Governance and Community Relations in Ghana Edmond Akwasi Agyeman, Emmanuel M. J. Tamanja & Bernard B. B. Bingab .................................................................................................... .............................................. 45 « Afrikki mwinda » : Y’en a marre, Balai citoyen, Filimbi et Lucha – catalyseurs d’une dynamique transafricaine de l’engagement citoyen Mamadou Dimé, Pascal Kapagama, Zakaria Soré & Ibrahima Touré ...............71 Aesthetic of Innocence: Experiencing Self-Filming by the San of Zimbabwe Oswelled Ureke, Nhamo A. Mhiripiri, Mercy Mangwana Mubayiwa & Ratidzo Midzi............................................................................................... .................................................93 Restructured Citizen–Government Relationship in Kenya's 2010 Constitution and the Right of Hawkers to the City in Nairobi Esther W. Kimani, Sammy G. Gachigua & George M. Kariuki........................ 117 Wars as Postcolonial African Illness in Uzodinma Iweala’s Beasts of No Nation Omon Osiki, Sola Owonibi & Oluyinka Ojedokun ................................................ 141 The Impact of Short Message Services (SMS) Weather Forecasts on Cost, Yield and Income in Maize Production: Evidence from a Pilot Randomised Controlled Trial in Bembèrèkè, North Benin Rosaine N. Yegbemey, Aline M. Aloukoutou & Ghislain B. D. Aïhounton........................................................................................... ......................... 163